2019
DOI: 10.4103/psychiatry.indianjpsychiatry_46_18
|View full text |Cite
|
Sign up to set email alerts
|

Depression in caregivers of patients with breast cancer: A cross-sectional study from a cancer research center in South India

Abstract: Context: Existing literature suggests an alarming rate of depression in cancer caregivers, which is comparable to or even higher than in patients themselves. There are no studies on depression among caregivers of breast cancer from India. Aims: The aim is to study the prevalence and determinants of depression in caregivers of breast cancer. Settings and Design: This is a cross-sectional study of 384 patient-caregiver dyads at a cancer researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…The progressive nature of advanced breast cancer and its treatment resulted in declining functional status which resulted in patients being unable to perform daily living activities such as grooming, groceries, and bathing. Our findings correspond with earlier research works which posit that caregivers of women diagnosed with advanced breast cancer provided support with activities of daily living [14,49].…”
Section: Discussionsupporting
confidence: 92%
“…The progressive nature of advanced breast cancer and its treatment resulted in declining functional status which resulted in patients being unable to perform daily living activities such as grooming, groceries, and bathing. Our findings correspond with earlier research works which posit that caregivers of women diagnosed with advanced breast cancer provided support with activities of daily living [14,49].…”
Section: Discussionsupporting
confidence: 92%
“…4,6,7 In the present study, majority of the care givers (91.55%) were from nuclear families. The findings were similar to a study done by Sreeja et al 8 In the present study, majority (71.56%) of the care givers were literates and (55.56%) were employed. The study also revealed that being involved in care providing, made some of the caregivers to quit from their livelihood wages.…”
Section: Discussionsupporting
confidence: 93%
“…The study also revealed that being involved in care providing, made some of the caregivers to quit from their livelihood wages. The findings are similar to studies by Kulkarni et al, Malathi et al, Sreeja et al [7][8][9] 4% 7% 16% 40%…”
Section: Discussionsupporting
confidence: 92%
“…Following the full-text screening, 107 were excluded because they did not meet the inclusion criteria as detailed in the PRISMA flow diagram. At the end of the screening procedure, 19 peer-reviewed citations remained for final inclusion in the review [3,4,6,10,15,[17][18][19][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The majority of the included studies (n = 15) used quantitative approaches [3,10,15,18,19,[23][24][25][26][27][28][30][31][32][33] and the remaining (n = 4) were qualitative studies [4,6,17,29]. Studies were conducted in the following countries: Nigeria (n = 2), Malaysia (n = 3), Ghana (n = 1), China (n = 3), Iran (n = 6), Turkey (n = 1), Mexico (n = 1), Indonesia (n = 1), and India (n = 1).…”
Section: Methodological Characteristics Of Included Studiesmentioning
confidence: 99%